2008
DOI: 10.1111/j.1529-8019.2008.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesotherapy for skin rejuvenation: assessment of the subepidermal low-echogenic band by ultrasound evaluation with cross-sectional B-mode scanning

Abstract: Skin-targeted ultrasound is a noninvasive technique that has been extensively used to evaluate age-related dermal changes, and the presence of a subepidermal low-echogenic band (SLEB) has been related to chronic UVR exposure in several studies. Since SLEB echogenicity is photoage-related, the aim of this study was to evaluate, through ultrasound imaging, the effects on skin photoaging of mesotherapy, a treatment approach currently used in cosmetic dermatology for skin rejuvenation. Twenty women (mean age: 46.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 20 publications
2
68
0
1
Order By: Relevance
“…They showed that this could be an effective treatment for skin photoaging. 58 Brown, 2006, stressed that, to date, the effects of mesotherapy have not been scientifically evaluated. He pointed that there was no dosage standardization and no treatment protocol.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that this could be an effective treatment for skin photoaging. 58 Brown, 2006, stressed that, to date, the effects of mesotherapy have not been scientifically evaluated. He pointed that there was no dosage standardization and no treatment protocol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Park et al, 2008, could not demonstrate the effectiveness of mesotherapy on body contouring using computed tomography scans to measure the cross-sectional areas and thickness of fat injected with a specific solution. 57 Lacarrubba et al, 2008, conducted a preliminary study to evaluate mesotherapy for skin rejuvenation and assessed the subepidermal low-echogenic band through ultrasound with cross-sectional B-mode scanning after multiple intradermal microinjections of hyaluronic acid salts weekly for four weeks. They showed that this could be an effective treatment for skin photoaging.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Laccaruba showed that topical HA is a very interesting treatment of human skin atrophy [37]. So, UV irradiation not only decreases the content of HA, but also the expression of CD44 receptors in mice [38] [39]. In 2015, Crisan et al [17] highlighted that vitamin C improves skin structure and reconstitutes the loss of interstitial collagen by using High Frequency Ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…In aesthetic medicine, skin-targeted ultrasound represents a noninvasive means of imaging pores, surface irregularities, and age-related dermal changes [13]. Features associated with photoaging, such as a subepidermal low-echogenic band, can be monitored before and after aesthetic medical procedures to determine their efficacy.…”
Section: High Frequency Ultrasoundmentioning
confidence: 99%